Impact of taxation on economic growth: evidence from Malaysia, developing and developed Asian countries - Joseph, Shalini Josephine (2019)
Economic growth has been a popular area of research as many authors have studied the various determinants of economic growth. In Asia, economic growth was brought when Western European capitalism started expanding their trade at a global scale. Since then, Asia started to grow rapidly and was known as one of the first regions to overcome the global financial crisis in 2008. After its rapid expansion, economic growth somewhat has remained between 5.5% to 6.0% from 2012 to 2016 without drastic changes. Taxation is one of the many determinants of growth as economic well-being of most countries are dependent on tax collection being the means for developing and providing public services.